REPRESENTASI KRISIS SEPEREMPAT ABAD TOKOH BAEK YI JIN DALAM DRAMA KOREA TWENTY FIVE TWENTY ONE - Zuhair Nizzah Izzul Haq; Syifa Syarifah Alamiyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The Korean drama Twenty Five Twenty One raises the issue of mental health, namely the emotional crisis that occurs in the quarter century of human life in their 20s, experiencing doubts about the future. This research focuses on the representation of the quarter life crisis experienced by the character Baek Yi Jin, who plays the role of the firstborn boy in his early 20s in the midst of the 1998 South Korean economic crisis in the Korean drama Twenty Five Twenty One. The research method is descriptive qualitative using John Fiske's semiotic analysis model through the level of reality, level of representation and level of ideology. The results showed that the influence of the Confucian ideology of cultural heritage is still deeply rooted in South Korean society with a traditional emphasis on social status, hierarchy, the role of each individual in social relations placing the roles and demands of early adult individuals triggering a quarter life crisis represented through the problems faced by Baek Yi Jin's character around the relationship between family, friends, romance, dreams and hopes, self-identity, work and career and contains values related to the scope of the quarter life crisis problem.